Flexible Asymmetric Supercapacitor Based on Structure‐Optimized Mn3O4/Reduced Graphene Oxide Nanohybrid Paper with High Energy and Power Density. (5th November 2015) - Hu, Yating; Guan, Cao; Feng, Guangxue; Ke, Qingqing; Huang, Xiaolei; Wang, John
Abstract : A highly flexible Mn3 O4 /reduced graphene oxide (rGO) nanohybrid paper with high electrical conductivity and high mass loading of Mn3 O4 nanofibers (0.71 g cm −3 ) is developed via a facile gel formation and electrochemical reduction process, which is low‐cost, environmental friendly, and easy to scale up. Confined Mn3 O4 nanofibers are well dispersed within the rGO sheets, which demonstrate to be a promising cathode material for flexible asymmetric supercapacitors (ASCs). When coupled with an electrochemically reduced rGO paper as the anode, a flexible ASC device, based on the Mn3 O4 /rGO nanohybrid paper as the cathode, is assembled; and it demonstrates remarkable electrochemical performance: a high volumetric capacitance of 54.6 F cm −3 (546.05 mF cm −2 ), and remarkable volumetric energy and power density (0.0055 Wh cm −3 and 10.95 W cm −3 ) being achieved with excellent cycling ability. The nanohybrid paper shows great improvement for flexible energy devices in terms of electrochemical properties. Abstract : A highly flexible Mn3 O4 /reduced graphene oxide (rGO) nanohybrid paper with high electrical conductivity and high mass loading of Mn3 O4 nanofiber (0.71 g cm −3 ) is successfully developed via a facile gel formation and electrochemical reduction process. Through this novel design and processing control, the energy and power density of the flexible Mn3 O4 /rGO‐based asymmetric supercapacitor are greatly improved.